What prospective scenarios for 2035 will be compatible with reduced impact of French beef and dairy farm on climate change?. (October 2017) - Mosnier, Claire; Duclos, Anne; Agabriel, Jacques; Gac, Armelle
Abstract: The agricultural sector is being called upon to reduce its greenhouse gas emissions (GHG). A scenario approach was developed to explore the plausible futures of the French bovine sector and their impact on climate change. These scenarios encompass a Business As Usual scenario (S1-BAU) and alternative contrasting scenarios: (S2) cattle production increase to meet a high global demand under a liberal policy, (S3) refocus on internal demand within France, with an upmarket move to 'green' products, (S4) committed public policy to reduce GHG emissions. This paper analyses how key drivers of these scenarios (e.g. subsidies on investment, reduction of market risks, carbon tax, limitation of concentrate feed in animal diets) affect the evolution of production, economics, and environmental impact on climate change of typical French suckler cow and dairy farms, by means of simulations performed with a bio-economic model. To adapt their farming systems to the scenarios, farms can opt for variably intensive/integrated practices per animal and per unit land area. Some technological progress in animal production, crop production, and farm equipment is also modeled. Results show that in S1-BAU, milk production, net income and impact on climate change of dairy farms rise. Beef production and impact on climate change decrease slightly in suckler cow farms. Impact on climate change per unit of product decreases owing to higher productivity per animal and to a more integrated management of crop production. Alternative scenarios underline that reorienting public support toward farm investment would further intensify dairy farms and increase their income, but would reduce production and income of suckler cow farms and favor crop production (S2). Climate change impact per unit of product is more strongly reduced in S3 (organic farming with low feed concentrate) than in S2, but with a reduced production, particularly for milk. A carbon tax decreases emissions, but to the detriment of cattle production, especially suckler cow farms. Highlights: Impact of contrasting socio-economic scenarios on the evolution of typical suckler cow and dairy farms has been assessed. GHG emissions per unit of output would be reduced. Dairy farms are likely to increase their production, for the BAU scenario and above all the liberal scenario. Dairy farms are likely to increase their production, for the S1-BAU scenario and above all S2 (liberal). S3 (organic) or S4 (carbon tax), reduce impact on climate change but with reduced milk and above all beef productions.